Comparative Effectiveness of Organic Fertilizer Types on Soybean Growth, Yield, and Soil Health in Sustainable Cultivation Systems - Indra Gunawan; Rahmi Dwi Handayani Rambe; Wanda Saputra; Nurhayati Nurhayati; Sri Hafnida Ritonga (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
Limitations in productivity and adverse impacts of chemical fertilizers highlight the need for sustainable solutions in soybean cultivation in Indonesia. This study aims to evaluate the effectiveness of organic fertilizers as an alternative to chemical fertilizers in sustainable agriculture-based soybean cultivation. The experimental method employed a Completely Randomized Design (CRD) with six treatments: control (no fertilizer), chemical fertilizer, goat manure, compost, biochar, and a combination of POC + compost. The parameters observed included plant height, number of effective root nodules, yield components (number of pods, weight of 100 seeds, yield per polybag), as well as changes in soil chemistry after harvest. The results showed that the treatment of goat manure (P2) and a combination of POC + compost (P5) gave the best results in improving soybean growth and yield. Both also showed significant improvements in soil pH, C-organic content, total nitrogen, and availability of P and K. In addition to increasing crop yields, organic fertilizers have also been proven to support increased soil microbial activity through the formation of effective root nodules. Thus, organic fertilizers have proven to be an effective and environmentally friendly alternative in replacing chemical fertilizers. The use of organic fertilizers can promote productive, efficient, and sustainable soybean farming.